26: CAPTURING TURKEYS WITH ORAL DRUGS* - Lovett E. Williams Jr.; David H. Austin; Tommie E. Peoples; Robert W. Phillips (Wildlife Society Bulletin)
ABSTRACT One technique to capture free‐ranging wild turkeys (Meleagris gallopavo) is to treat baits with alpha‐chloralose, methoxymol, or tribromoethanol. In this study approximately 1,600 turkeys were captured with alpha‐chloralose with 9.0 percent mortality; 113 were captured with methoxymol with a mortality rate of 6.3 percent; and 209 were captured with tribromoethanol with a mortality rate of 2.4 percent. Turkeys could be captured approximately 15 minutes after beginning to feed on bait treated with tribromoethanol, and they usually recovered within 10 hours. Alpha‐chloralose produced narcosis much more slowly, and its effects often continued more than 40 hours. The narcotic characteristics of methoxymol and tribromoethanol were similar, but methoxymol was difficult to procure in sufficient quantities and turkeys often refused to eat it because of its taste.